2014
DOI: 10.1299/mej.2014smm0010
|View full text |Cite
|
Sign up to set email alerts
|

Joule heat welding of thin wires to thin films

Abstract: To effectively use micro or nano materials and create advanced materials systems from them, welding techniques for such small scale materials are vital. For this purpose, the tips of two thin wires were welded together with Joule heat and the conditions required to achieve it was discovered experimentally. In this paper, the Joule heat welding of thin wires to thin films deposited on substrates is described. To derive the conditions required to achieve this, a heat conduction model for a cylindrical element in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Welding the end of one thin wire to the side of another to create complex wire structures by repeatedly carrying out the welding process has also been done. 27) Moreover, Joule heat welding of thin wires with different thicknesses, 28) and that of wires to substrates 29) have also been reported. To expand the applicability of the Joule heat welding technique, not only welding similar metals, but also welding dissimilar metal materials is very much demanded.…”
Section: Introductionmentioning
confidence: 95%
“…Welding the end of one thin wire to the side of another to create complex wire structures by repeatedly carrying out the welding process has also been done. 27) Moreover, Joule heat welding of thin wires with different thicknesses, 28) and that of wires to substrates 29) have also been reported. To expand the applicability of the Joule heat welding technique, not only welding similar metals, but also welding dissimilar metal materials is very much demanded.…”
Section: Introductionmentioning
confidence: 95%
“…It has been reported that thin Pt wires are welded together in self-completed matter under the supply of constant direct current (Tohmyoh and Fukui, 2009). Tip of a thin wire was welded to the side of another thin wire (Fukui and Tohmyoh, 2011) or the surface of the substrate (Tohmyoh and Fujimori, 2014). Thin wires having dissimilar diameter (Fujimori and Tohmyoh, 2013) and dissimilar metal wires were also welded together by Joule heating (Tohmyoh and Sunagawa, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The study has reported surface plasmon propagation along a single metal nanowire (Ditlbacher et al 2005;Ye et al 2015). Micro/nanoscale systems using micro/nanowires are assembled by organizing and welding wires with each other (Whang et al 2003;Garnett et al 2012;Tohmyoh and Fujimori 2014). These micro/nanoscale systems are created due to the development of various growth methods such as the electrodeposition growth method (Motoyama et al 2005), the template growth method (Cao and Liu 2008;Yao et al 2011), and chemical synthesis (Schmädicke et al 2014).…”
Section: Introductionmentioning
confidence: 99%